Sensory characteristics and chemical composition of pink shrimp (Farfantepenaeus brasiliensis) smoked with the presence and absence of the carapace - Silva, Thiberio Carvalho da; Rocha, Joana D´Arc Maurício; Santos, Vagner Gerônimo do Nascimento; Bridi, Vinicius Ricardo Calcagno; Signor, Altevir; Boscolo, Wilson Rogério (Scientia Agraria Paranaensis, 2017)
The objective of this study was to evaluate the smoking process in pink shrimp (Farfantepenaeus brasiliensis) prepared with and without the shell, through the proximal composition and sensory characteristics. Thus, we used 60 tails (abdomen) shrimp with individual average weight of 16.67 g, were divided into two treatments, with and without shell. After curing, they were evaluated sensorily, with 30 tasters, using a simple stimulation method and 90 g samples were stored (-15 ºC) for later analysis of proximal composition. The smoked shrimp showed average values of crude protein (28.93%), moisture (62.15%), lipids (1.30%) and ash (8.14%) higher than shrimp in natura (88.72%, 10.36%, 0.43% and 0.92%, respectively). There was no effect of the presence or absence of the shell in the proximal composition of smoked shrimp (p < 0.05). Regarding the sensory evaluation, the tasters showed preference to shrimp samples with no shell, through the grades given in the analysis. Among the characteristics evaluated were no differences (p < 0.05) in appearance and flavor. The smoking process positively changed the proximal composition of shrimp and were approved by the tasters.